Effects of dietary palygorskite supplementation on the growth performance, oxidative status, immune function, intestinal barrier and cecal microbial community of broilers - Du, Mingfang; Chen, Yueping; Wang, Shiqi; Zhao, Haoran; Wen, Chao; Zhou, Yanmin (Frontiers in Microbiology, 2022)
The present study aimed to investigate the effects of palygorskite (PAL) as an alternative to antibiotic on the growth performance, oxidative status, immune function, intestinal barrier and cecal microbial community of broilers. A total of 360 one-day-old male Ross-308 broilers were randomly allotted to three treatments with eight replicates. Broilers in the three groups were designated as follows: basal diet (CON group), basal diet+50 mg/kg chlorotetracycline (ANT group), and basal diet+ 10 g/kg PAL (PAL group). Supplementing PAL reduced feed to gain ratio in broilers during 22 to 42 days of age (P<0.05), with its value being similar to that of the ANT group (P>0.05). Broilers fed a PAL-supplemented diet exerted decreased contents of interferon-γ (IFN-γ) and interleukin-1β in serum, and the same reduction was found in jejunal IFN-γ level, when compared to the CON group (P<0.05). Moreover, compared with the CON group, broilers after PAL treatment had a lower malondialdehyde content in jejunal mucosa (P<0.05). Supplementing PAL elevated jejunal villus height (VH) and ratio of VH to crypt depth compared with the ANT group (P<0.05). Cecal microbiota communities among the three groups were significant different, as demonstrated by distinct clusters from partial least squares discriminant analysis, although dietary treatments had no significant effect on the bacterial richness and diversity indices (P>0.05). At genus level, the addition of PAL increased the relative abundance of norank_f__Barnesiellaceae and decreased that of unclassified_f__Oscillospiraceae in cecal digesta compared with those in the CON group (P<0.05); the proportion of genus norank_f__Barnesiellaceae was increased by PAL treatment when compared with the ANT group (P<0.05). Moreover, spearman’s correlations showed that the modulation of cecal microflora composition by PAL supplementation was closely correlated with the promotion of growth performance (feed to gain ratio) and intestinal health-related (contents of malondialdehyde and IFN-γ, and VH value in jejunum) variables of broilers (P<0.05). Taken together, dietary PAL could improve the growth performance, antioxidant capacity, and immune status, as well as intestinal barrier function in broilers, which might be partially associated with the alteration of cecal microbiota. Moreover, dietary PAL may be a promising alternative to antibiotic growth promoter for broilers.